Potential of Flavonoids on Aortic Histopathological Improvement of ApoE-/- Mice With High-Fat Diet: A Systematic Literature Review - Adyatma, Hilmi; Hardini, Niniek; Thadeus, Maria Selvester (Universitas Muhammadiyah Sumatera Utara, 2021)
Non-communicable diseases account for more than 36 million deaths every year (63% of all deaths). Globally, non-communicable diseases (NCDs) that cause the most deaths each year are cardiovascular diseases. One of the cardiovascular diseases is coronary heart disease. The cause of coronary heart disease is acute coronary syndrome. More than 90% of acute coronary syndromes (ACS) are the result of atherosclerotic disorders. Therefore, research on the potential of flavonoids to improve histopathology of atherosclerosis needs to be carried out in order to provide information about alternative drugs that can be used by patients. The purpose of this research using a systematic literature review research methodology is to identify the potential of flavonoids to improve aortic histopathology in ApoE-/- mice with a high-fat diet. Systematic literature review by conducting a literature search using PubMed and Google Scholar. Literature that discusses flavonoids, ApoE-/- mice, high-fat diet, aorta, and atherosclerosis. There were 8 studies which concluded that flavonoids could inhibit or reduce the enlargement or further formation of aortic atherosclerotic plaques in ApoE-/- mice on a high-fat diet. Flavonoids have the potential to inhibit or reduce the enlargement or further formation of aortic atherosclerotic plaques in ApoE-/- mice on a high-fat diet.